2021
DOI: 10.21894/jopr.2021.0008
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Bacterial Communities Determined by Culture-Dependent and-Independent Approaches in Oil Palm Planted on Tropical Peatland

Abstract: A combination of deoxyribonucleic acid (DNA)-based method and sequencing technologies have initiated a new era of soil microbial ecology to examine the patterns of bacterial communities in tropical peatland. The aims of the study are to verify and compare the bacterial communities in a 12-year-old oil palm plantation on peat of Sibu, Sarawak, Malaysia using culture-dependent and culture-independent approaches. The bacterial diversity identified from both approaches were amplified using 16S ribosomal deoxyribon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Moreover, this method provides limited information on microbial communities because more than 99% soil microorganisms remain 'unculturable' in the laboratory as they require specific growth conditions. As a result, a large proportion of microbial communities remains unexplored, and organisms such as Acidobacteria are underrepresented in isolated cultures (Ayob and Kusai, 2021;Liu et al, 2006) when compared to the molecular methods. The molecular methods that describe communities dominated by predominantly uncultivated microorganisms' groups that are not detected by culture, provide a more rapid result, less time-consuming, and been shown to have great flexibility in terms of gene target and target region (Montalvo et al, 2014;Rudkjøbing et al, 2016).…”
Section: P R E S S Culture-dependent Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, this method provides limited information on microbial communities because more than 99% soil microorganisms remain 'unculturable' in the laboratory as they require specific growth conditions. As a result, a large proportion of microbial communities remains unexplored, and organisms such as Acidobacteria are underrepresented in isolated cultures (Ayob and Kusai, 2021;Liu et al, 2006) when compared to the molecular methods. The molecular methods that describe communities dominated by predominantly uncultivated microorganisms' groups that are not detected by culture, provide a more rapid result, less time-consuming, and been shown to have great flexibility in terms of gene target and target region (Montalvo et al, 2014;Rudkjøbing et al, 2016).…”
Section: P R E S S Culture-dependent Approachmentioning
confidence: 99%
“…On the other hand, Trichoderma harzianum (Figure 2h) has biocontrol properties against devastating oil palm disease; basal stem rot caused by Ganoderma boninense, and has widely been used as a biofertiliser to reduce disease incidence in oil palm plantations (Naher et al, 2012;Sundram et al, 2008). Meanwhile, the most isolated bacteria in the oil palm plantations of Sarawak are Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes (Ayob and Kusai, 2021;Kusai and Ayob, 2020). Isolated bacteria Burkholderia cepacia (class Betaproteobacteria) has been used as a biocontrol agent to reduce incidene of basal stem rot in oil palm by 42%.…”
Section: P R E S S Culture-dependent Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Amit et al (2021) concluded that bird species diversity, abundance and their feeding guild can be improved by letting ground layer vegetation grow naturally and maintaining the water quality of the drainage system in the early stage of oil palm development to attract birds which prefer this habitat. Ayob et al (2021) recovered 227 bacterial isolates belonging to four major phyla (22 genera) from culturedependent and -independent approaches in oil palms planted on tropical peatland.…”
Section: Precision Agriculture Using Digital Technologies In Oil Palm...mentioning
confidence: 99%